Dimensi Pneumatik dalam Ruang Publik: Studi Eksposisi Kisah 4:1-22 - Lidia J. F. Sondakh; Marthinus Seobele (KHARISMATA: Jurnal Teologi Pantekosta, 2025)
This article explores the manifestation of the pneumatic dimension in Acts 4:1–22, with a particular focus on the role of the Holy Spirit in the speech and actions of Peter and John in the public sphere, as they faced institutional pressure from the Sanhedrin. Employing a theological and exegetical approach, the article argues that the proclamation of the Gospel in the context of religious conflict cannot be separated from the active role of the Holy Spirit, who imparts courage, wisdom, and prophetic authority to the apostles. The discussion engages with various theological perspectives, including Craig Keener, who views the Spirit’s role as a continuation of Jesus’ ministry; Michael Green, who highlights the transformation from fear to boldness; and James D.G. Dunn, who emphasises the internal process of spiritual formation. The article also responds to charismatic interpretations that tend to limit the Spirit’s role to supernatural manifestations. In contrast, the author asserts that the pneumatic dimension encompasses integrity in witness, steadfastness in suffering, and contextual awareness in mission. This study is particularly relevant to the contemporary church, which faces the challenges of religious pluralism and the need for faithful and courageous Gospel proclamation. The Holy Spirit remains the source of power sustaining Christian witness both historically and today.     Artikel ini mengeksplorasi manifestasi dimensi pneumatik dalam Kisah Para Rasul 4:1–22, dengan fokus pada peran Roh Kudus dalam perkataan dan tindakan Petrus dan Yohanes di ruang publik saat menghadapi tekanan institusional dari Sanhedrin. Dengan pendekatan teologis dan eksegetis, artikel ini menunjukkan bahwa pewartaan Injil dalam konteks konflik religius tidak dapat dilepaskan dari peran aktif Roh Kudus, yang memberi keberanian, hikmat, dan otoritas profetik kepada para rasul. Diskusi ini mengangkat berbagai pandangan teolog, seperti Craig Keener yang melihat peran Roh sebagai kelanjutan pelayanan Yesus, Michael Green yang menekankan transformasi dari ketakutan menjadi keberanian, hingga James D.G. Dunn yang menyoroti proses internal formasi spiritual. Artikel ini juga menanggapi pendekatan karismatik yang cenderung membatasi peran Roh pada manifestasi supranatural. Sebaliknya, penulis menegaskan bahwa dimensi pneumatik mencakup integritas dalam bersaksi, keteguhan dalam penderitaan, dan kesadaran kontekstual dalam misi. Studi ini relevan dalam konteks gereja masa kini yang menghadapi tantangan pluralisme dan kebutuhan akan pewartaan Injil yang setia dan berani. Roh Kudus tetap menjadi sumber kuasa yang menopang kesaksian Kristen dalam sejarah dan masa kini.